2011
DOI: 10.1155/2011/258365
|View full text |Cite
|
Sign up to set email alerts
|

ADAM23, a Gene Related to LGI1, Is Not Linked to Autosomal Dominant Lateral Temporal Epilepsy

Abstract: Autosomal dominant lateral temporal epilepsy (ADTLE) is an inherited epileptic syndrome characterized by ictal auditory symptoms or aphasia, negative MRI findings, and relatively benign evolution. Mutations responsible for ADLTE have been found in the LGI1 gene. The functions of the Lgi1 protein apparently are mediated by interactions with members of the ADAM protein family: it binds the postsynaptic receptor ADAM22 to regulate glutamate-AMPA currents at excitatory synapses and also the ADAM23 receptor to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Genetic disorders that are caused by defects in a ligand for a particular receptor are frequently mirrored by disorders in which that receptor is deficient. However, a causative role for ADAM22 and ADAM23 in ADLTE has been questioned in genetic studies of families without LGI1 mutations: direct sequencing of ADAM22 exons revealed no disease-causing mutations [ 34 , 35 ], and linkage analysis with microsatellite markers within or near the ADAM23 gene failed to reveal any significant linkage peak [ 36 ]. The absence of causative mutations in ADAM22 and ADAM23 , however, is not in contrast with their involvement in the molecular pathway underlying ADLTE, and this apparent contradiction can be explained in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic disorders that are caused by defects in a ligand for a particular receptor are frequently mirrored by disorders in which that receptor is deficient. However, a causative role for ADAM22 and ADAM23 in ADLTE has been questioned in genetic studies of families without LGI1 mutations: direct sequencing of ADAM22 exons revealed no disease-causing mutations [ 34 , 35 ], and linkage analysis with microsatellite markers within or near the ADAM23 gene failed to reveal any significant linkage peak [ 36 ]. The absence of causative mutations in ADAM22 and ADAM23 , however, is not in contrast with their involvement in the molecular pathway underlying ADLTE, and this apparent contradiction can be explained in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…This perspective is fascinating because other pre- or postsynaptic membrane-bound proteins (ADAM22, ADAM23, and Kv1 channel genes) have been explored before in search for mutations in EAF, but no mutations were detected. 8 10 …”
Section: Discussionmentioning
confidence: 99%
“…No mutation in genes other than LGI1 has been identified so far in EAF. 7 10 The advent of next-generation sequencing has made the identification of causal variants possible even in small families. In this study, we describe a comprehensive whole-exome sequencing (WES) approach that enabled us to identify likely pathogenic variants in EAF probands and their affected relatives, demonstrating genetic heterogeneity underlying this epilepsy phenotype.…”
mentioning
confidence: 99%